P021: Impact of emergency department surge and end of shift on patient workup and treatment prior to referral to internal medicine. (2nd June 2016) - Charbonneau, V.; Stiell, I.G.; Kwok, E.S.; Boyle, L.
Abstract : Introduction: The goal of this study was to determine if emergency department (ED) surge and end of shift assessment of patients affect the extent of diagnostic tests, therapeutic interventions performed and accuracy of diagnosis prior to referral of patients to Internal Medicine as well as the impact on patient outcomes.Methods: This study was a health records review of consecutive patients referred to the internal medicine service with an ED diagnosis of heart failure, COPD or sepsis, at two tertiary care EDs. We developed a scoring system in consultation with senior emergency and internal medicine physicians to uniformly assess the treatments and investigations performed for patients diagnosed in the ED with heart failure, COPD or sepsis. These scores were then correlated with surge levels and time of day at patient assessment and disposition. Rate of admission and diagnosis disagreements were also assessed.Results: We included 308 patients (101 with heart failure, 101 with COPD, 106 with sepsis). Comparing middle of shift to end of shift, the overall weighted mean scores were 92.2% vs. 91.7% for investigations and 73.5% vs. 70.0% for treatments. Comparing low to high surge times, the overall weighted mean scores were 89.9% vs. 92.6% for investigations and 68.6% vs. 71.7% for treatments. Evaluating each condition separately for investigations and treatments according to time of shift or surge conditions, there were no consistent differences in scores. We found overall high admission rates (93.1 % for heart failure, 91.1% for COPD, 96.2% for sepsis patients), and low rates of diagnosis disagreement (4.0 % heart failure, 10.9% COPD, 8.5% sepsis).Conclusion: We found that surge levels and end of shift did not impact the extent of investigations and treatments provided to patients diagnosed in the emergency department with heart failure, COPD or sepsis and referred to internal medicine. Admission rates for the patients referred were above 90% and there were very few diagnosis disagreements or diversion to alternate service by internal medicine. We believe this supports the emergency physician's ability to adapt to time and surge constraints, particularly in the context of commonly encountered conditions.